Analisis Buku Tematik Kelas IV SD Berdasarkan Multiple Intelegence - Rambe, Amalia Ulfa; Sukmawarti, Sukmawarti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Thematic books are books that summarize various materials with different characteristics. Thematic books are textbooks that are different from other books where in one book there are several types of other subjects and are interrelated from the beginning of the subtheme to the end of the sub-theme. In this case the researcher tries to research and find out the type of MultipleIntelligence contained in the thematic book. This research method uses qualitative methods, thetype of approach in research is a literature study approach. The subject of the research is thethematic package book in class IV, the analysis is carried out on multiple intelligence on theme 4.The data collection techniques are carried out in the form of observation, interview, anddocumentation techniques. Based on the results of the analysis that has been carried out byresearchers, it is found that linguistic intelligence is the dominant intelligence among all existingintelligences. As many as 33.3% linguistic intelligence, 25% interpersonal intelligence and logical mathematical intelligence as much as 16.7% on interpersonal intelligence students will further develop their character, especially to socialize with the community. So that linguistic intelligence is found to be the dominant intelligence. This research will also later be useful for teachers and researchers to be used as a reference in further research.